Nurses' performance in welcome to spontaneous demand in Family Health Strategy (Research, Society and Development, 2022)
Introduction: Welcoming is a resource designed to support the qualification of the health system, as it provides the user with access to fair, expanded and comprehensive care, and this access is a fundamental human right. This study aims to Understand The role of nurses in the process of welcoming spontaneous demand in Basic Health Units with the Family Health Strategy. Methodology: This is an exploratory, descriptive study with a qualitative approach, carried out through semi-structured interviews with nurses from basic units. Data were collected in 2016 and analyzed through the Thematic Content Analysis proposed by Bardin. Results: From the content analysis, three categories emerged: Conceptions about user embracement; Difficulties and facilities for carrying out the reception; Team active in the reception. It was observed that, despite the interviewees' knowledge, they are unable to organize the reception as recommended in their daily lives due to the difficulties listed by them, such as the physical structure and the large spontaneous demand. Final Considerations: For the reception to be of quality and resolute, professionals will have to expand the listening time, create bonds and carry out programmatic actions with the population to solve problems with the repressed demand.